Evaluation of knowledge, attitude and practice of pharmacovigilance among interns and nursing students in a tertiary care teaching hospital - Pawar, Sudhir R.; Gawari, Nitin C.; Lokhande, Jaisen M. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Even though the role of spontaneous reporting of adverse drug reactions (ADRs) is well established in pharmacovigilance, it is not followed in the practice and a large number of ADRs goes unreported. In our institute, almost all of the ADR reported to the department of pharmacology are through either the faculty members or the residents and very few by the nurses and interns. Methods: The current survey was thus conducted to assess the knowledge, attitude and practice (KAP) of nursing students and interns. It is expected that the results should help us to designs specific activities to improve ADR reporting. The study was a questionnaire based survey to assess the knowledge, attitude and practices (KAP) of the interns (n=74) and nursing students (n=108) regarding ADR reporting and pharmacovigilance in this tertiary care centre. Results: More interns gave correct responses to knowledge based and attitude based questions of pharmacovigilance compared to the nursing students. On the other hand, more nursing students came across ADRs in the patients compared to interns. Even though 93.24% interns responded to have got training on “how to report ADRs”, only 6.76% ever reported ADR to pharmacovigilance centre. Conclusions: Proper training on pharmacovigilance, with easy way for reporting ADRs would be a useful step in improving pharmacovigilance status in nursing students and interns.